Peran Remaja Masjid Terhadap Kesadaran Masyarakat Dalam Mengelola Kebersihan di Masjid Al-Husna Palangka Raya - Muhammad Khair; Muhammad Iqbal (Yayasan Cendekia Gagayunan Indonesia, 2025)
This service aims to increase public awareness of the importance of mosque cleanliness through the active role of mosque youth as agents of change. The activity was carried out at the Al-Husna Mosque, Palangka Raya, using an educational and participatory approach. The methods used included initial observation, installation of posters appealing for cleanliness, and routine cleaning actions carried out by mosque youth without direct community involvement. The results of the activity showed that the involvement of mosque youth was able to build a culture of concern for the cleanliness of the worship environment. Youth are not only implementers, but also inspirators of social change, although there are still challenges in the form of low community participation in general. This activity is expected to be an example for other mosques in forming collective awareness and a sustainable clean culture.